Predictive and prescriptive analytics in healthcare: a survey - Lopes, João António Araújo (2020)
Over the years, health area has received numerous studies on how to improve its management and administration activities and, fundamentally, the Healthcare provided to its patients. Currently, there is an exponential growth of data in the health system. In this sense, it is crucial the implementation of technologies capable of using it in a beneficial way for the organization, helping it to fulfill its strategic objectives. Subsequently, this same data, if used correctly, has the capacity to assist the organization at an administrative level, as well as at the level of patient care, using predictive and optimization models capable of revolutionizing the current health system. Thus, this article aims to identify the advances that have been made in this area, focusing on the development of predictive and optimization techniques, applied in Health, and how these can improve the lives of managers, doctors and patients.